Characterization and Functional Analysis of the Poplar Pectate Lyase-Like Gene PtPL1-18 Reveal Its Role in the Development of Vascular Tissues - Bai, Yun; Wu, Dan; Liu, Fei; Li, Yuyang; Chen, Peng; Lu, Mengzhu; Zheng, Bo (Frontiers in Plant Science, 2017)
Pectin is a major component of plant cell walls, and the structure of pectin impacts on the properties of wood. Although we know that pectate lyase (PL, EC 4.2.2.2) has a major influence on the structure of pectin, our knowledge of Pectate lyase-like genes (PLL) in tree species remains limited. To better understand the characteristics of PLL genes in trees and to identify novel PLL genes that are potentially involved in the development of wood, we performed comprehensive analyses of gene structures, phylogenetic relationships, chromosomal locations, gene duplication events, conserved protein motifs, and gene expression patterns of 30 PLLs in Populus trichocarpa (PtPL1s). We performed an in silico gene expression profiling and quantitative real time-PCR analysis and found that most of the PtPL1 genes from subgroup Ia and Ib were highly expressed in xylem. PtPL1-18 from subgroup Ia was preferentially expressed in developing primary xylem and in xylem cells that were developing secondary walls. Overexpression of PtPL1-18 in poplar reduced plant growth and xylem development. Reduced secondary cell wall thickening and irregular xylem cells were observed in the transgenic trees, probably due to their lower pectin content. Although pectin is not a major component of plant secondary cell walls, our results are consistent with the PtPL1 genes performing important functions during wood formation.